2020
DOI: 10.1609/aaai.v34i04.5835
|View full text |Cite
|
Sign up to set email alerts
|

TellTail: Fast Scoring and Detection of Dense Subgraphs

Abstract: Suppose you visit an e-commerce site, and see that 50 users each reviewed almost all of the same 500 products several times each: would you get suspicious? Similarly, given a Twitter follow graph, how can we design principled measures for identifying surprisingly dense subgraphs? Dense subgraphs often indicate interesting structure, such as network attacks in network traffic graphs. However, most existing dense subgraph measures either do not model normal variation, or model it using an Erdős-Renyi assumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Shin, Eliassi-Rad, and Faloutsos (2016) showed empirical patterns in real-world graphs related to k-cores. Recently, it has been observed that the subgraphs of the detected core users are used for several graph-related tasks, such as community detection (Peng, Kolda, and Pinar 2014), dense-subgraph detection (Hooi et al 2020) etc. We encourage the readers to go through Malliaros, Papadopoulos, and Vazirgiannis (2016) for a comprehensive survey on network core detection.…”
Section: Related Workmentioning
confidence: 99%
“…Shin, Eliassi-Rad, and Faloutsos (2016) showed empirical patterns in real-world graphs related to k-cores. Recently, it has been observed that the subgraphs of the detected core users are used for several graph-related tasks, such as community detection (Peng, Kolda, and Pinar 2014), dense-subgraph detection (Hooi et al 2020) etc. We encourage the readers to go through Malliaros, Papadopoulos, and Vazirgiannis (2016) for a comprehensive survey on network core detection.…”
Section: Related Workmentioning
confidence: 99%
“…Note that although CPD works well at some densities, it fluctuate greatly, indicating that CPD is not very suitable for ML behavior detection. Flow Surprisingness estimation with extreme value theory: Inspired by [4], we use Generalized Pareto (GP) Distribution, a commonly used probability distribution within extreme value theory, to estimate the extreme tail of a distribution without making strong assumptions about the distribution it- self. GP distributions exhibit heavy-tailed decay (i.e.…”
Section: Q2 Performance On Real-world Datamentioning
confidence: 99%